Attitudes of pharmacy students and alumni of the faculty of pharmacy in relation to the position of the pharmaceutical profession in society - Ćirić, Milan; Krajnović, Dušanka; Šesto, Sofija; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
The position of pharmacists in Serbia has changed through periods of learning a professional role, complete professionalization and deprofessionalization. Solemn ceremony during faculty enrollment is important strategy for creating a sense of connection with the profession and strengthening its identity, as well as professional socialization of pharmacists. The aim of this research is to examine attitudes of students and alumni regarding the position of pharmaceutical profession in society. A cross-sectional study design with purpose-built questionnaire was used. Data were over a period of three months. 409 subjects participated, of which 140 were alumni, predominantly female (84.8%). Most respondents (86.8%) answered that pharmaceutical profession is not sufficiently valued in society or by other medical professions (79.2%) and the importance of pharmacists for patient healthcare is not sufficiently recognized (76.8%). The majority of respondents believe that public and other healthcare professionals do not recognize the knowledge of pharmacists for optimization of therapeutic outcomes (86%, 76.3% respectively). Introducing a solemn ceremony for students at admission, and taking the oath after studies was supported by 66.2% and 84.1% respondents, respectively, in response to growing challenges of deprofessionalization. Poor social status perception of pharmacy has been recognized together with importance of maintaining a professional environment at the faculty. Pharmacy students cannot become professionals immediately after receiving university degree or license to work. In order to become professionals, during their studies students need to recognize and become professionally sensitive to all the factors that make pharmacy specific, and set it apart from other healthcare professions.